The factors influence the contribution of Liquified Natural Gas (LNG) production to the Malaysian economy / Norazmah Abdul - Abdul, Norazmah (2016)
This paper study is consists of the factors influencing the contribution of LNG production to the contribution Malaysian economy. The oil and gas sector has been contributing significantly to the Malaysia’s in the economy term of its contribution toward economy in Malaysia. The factors that are included in this study is LNG production, LNG export production and LNG consumption. LNG production is continuously increases year by year since the first production on 1982. Production of LNG in Malaysia is more quality and cheaper than other country that produce LNG because of MLNG Satu, MLNG Dua and MLNG Tiga are increases the technology in processing the LNG production and delivering the demand especially Japan thru pipeline that was reduce the cost of production of LNG.